2009
DOI: 10.1158/1078-0432.ccr-09-0213
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 Inhibitor BIIB021 (CNF2024) Depletes NF-κB and Sensitizes Hodgkin's Lymphoma Cells for Natural Killer Cell–Mediated Cytotoxicity

Abstract: Purpose: In Hodgkin's lymphoma, constitutive activation of NF-κB promotes tumor cell survival and proliferation. The molecular chaperone heat shock protein 90 (HSP90) has immune regulatory activity and supports the activation of NF-κB in Hodgkin's lymphoma cells. Experimental Design: We analyzed the effect of HSP90 inhibition on viability and NF-κB activity in Hodgkin's lymphoma cells and the consequences for their recognition and killing through natural killer (NK) cells. Results: The novel orally administrab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…Our data showed that BIIB021 could inhibit Akt protein expression and phosphorylation. Additionally, BIIB021 had a modest effect on p65 expression, a transcription factor of the NF-κB family ( Figure 2B), consistent with a previous report that BIIB021 inhibits constitutive NF-κB activity in Hodgkin's lymphoma cells [11] . Interestingly, dose-dependent decreases in the total MDM2 and phospho-MDM2 protein levels in the BIIB021-treated cells were observed by Western blotting.…”
Section: Biib021 Induces Molt-4 Apoptosissupporting
confidence: 91%
See 1 more Smart Citation
“…Our data showed that BIIB021 could inhibit Akt protein expression and phosphorylation. Additionally, BIIB021 had a modest effect on p65 expression, a transcription factor of the NF-κB family ( Figure 2B), consistent with a previous report that BIIB021 inhibits constitutive NF-κB activity in Hodgkin's lymphoma cells [11] . Interestingly, dose-dependent decreases in the total MDM2 and phospho-MDM2 protein levels in the BIIB021-treated cells were observed by Western blotting.…”
Section: Biib021 Induces Molt-4 Apoptosissupporting
confidence: 91%
“…By binding to the ATP-binding pocket of Hsp90, BIIB021 induces the degradation of Hsp90 client proteins, including HER-2, Akt, and Raf-1, and results in the inhibition of tumor growth [10] . In addition, BIIB021 was found to inhibit the growth of Hodgkin's lymphoma (HL) cells by depleting NF-κB activity and sensitizing the cells to natural killer cell-mediated cytotoxicity [11] . Furthermore, it has been reported that combination therapy using BIIB021 plus radiotherapy or chemotherapy could benefit cancer treatment [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…81 Notably, Hsp90 inhibitors have been found to suppress NF-kB activity. 82 A CD30-directed antibody-drug conjugate could be a good option given frequent CD30 expression in EBV-positive DLBCL patients. A recent trial of Brentuximab Vedotin in 2 cases of EBV-positive DLBCL did not show promising results, but the small size trial might not be representative.…”
Section: Novel Therapeutic Approachesmentioning
confidence: 99%
“…The best-known purinebased Hsp70-inducer to date is BIIB021 (also named CNF-2024), which has been demonstrated to be a potent Hsp90-inhibitor and is currently in phase 2 clinical studies in its orally administered form Porter et al 2010). One study indicates that BIIB021 may be a potent anti-inflammatory, suppressing the NF-kB pathway in Hodgkin's lymphoma (Boll et al 2009). However, it is yet undetermined whether this or other purine-based compounds produce the same effect in other cell types or disease states or if they can permeate the BBB.…”
Section: Role For Hsps In Therapy and Hsp70-inducing Pharmaceuticalsmentioning
confidence: 99%